Soil acidification and salinity: the importance of biochar application to agricultural soils - Huang, Kai; Li, Mingquan; Li, Rongpeng; Rasul, Fahd; Shahzad, Sobia; Wu, Changhong; Shao, Jinhua; Huang, Guoqin; Li, Ronghui; Almari, Saad; Hashem, Mohamed; Aamer, Muhammad (Frontiers in Plant Science, 2023)
Soil acidity is a serious problem in agricultural lands as it directly affects the soil, crop production, and human health. Soil acidification in agricultural lands occurs due to the release of protons (H+) from the transforming reactions of various carbon, nitrogen, and sulfur-containing compounds. The use of biochar (BC) has emerged as an excellent tool to manage soil acidity owing to its alkaline nature and its appreciable ability to improve the soil's physical, chemical, and biological properties. The application of BC to acidic soils improves soil pH, soil organic matter (SOM), cation exchange capacity (CEC), nutrient uptake, microbial activity and diversity, and enzyme activities which mitigate the adverse impacts of acidity on plants. Further, BC application also reduced the concentration of H+ and Al3+ ions and other toxic metals which mitigate the soil acidity and supports plant growth. Similarly, soil salinity (SS) is also a serious concern across the globe and it has a direct impact on global production and food security. Due to its appreciable liming potential BC is also an important amendment to mitigate the adverse impacts of SS. The addition of BC to saline soils improves nutrient homeostasis, nutrient uptake, SOM, CEC, soil microbial activity, enzymatic activity, and water uptake and reduces the accumulation of toxic ions (Na and Cl). All these BC-mediated changes support plant growth by improving antioxidant activity, photosynthesis efficiency, stomata working, and decrease oxidative damage in plants. Thus, in the present review, we discussed the various mechanisms through which BC improves the soil properties and microbial and enzymatic activities to counter acidity and salinity problems.